HIF factors cooperate with PML‐RARα to promote acute promyelocytic leukemia progression and relapse - Nadia Coltella; Stefano Percio; Roberta Valsecchi; Roberto Cuttano; Jlenia Guarnerio; Maurilio Ponzoni; Pier Paolo Pandolfi; Giovanni Melillo; Linda Pattini; Rosa Bernardi (EMBO Molecular Medicine)
Abstract Acute promyelocytic leukemia (APL) is epitomized by the chromosomal translocation t(15;17) and the resulting oncogenic fusion protein PML‐RARα. Although acting primarily as a transcriptional repressor, PML‐RARα can also exert functions of transcriptional co‐activation. Here, we find that PML‐RARα stimulates transcription driven by HIF factors, which are critical regulators of adaptive responses to hypoxia and stem cell maintenance. Consistently, HIF‐related gene signatures are upregulated in leukemic promyelocytes from APL patients compared to normal promyelocytes. Through in vitro and in vivo studies, we find that PML‐RARα exploits a number of HIF‐1α‐regulated pro‐leukemogenic functions that include cell migration, bone marrow (BM) neo‐angiogenesis and self‐renewal of APL blasts. Furthermore, HIF‐1α levels increase upon treatment of APL cells with all‐trans retinoic acid (ATRA). As a consequence, inhibiting HIF‐1α in APL mouse models delays leukemia progression and exquisitely synergizes with ATRA to eliminate leukemia‐initiating cells (LICs).